Use of antidepressants in childhood and adolescence (Research, Society and Development, 2022)
This work brings reflections on a delicate subject, because when the object of study is child and adolescent, it is necessary to established a detailed medical history for the short-term drug introduction, because children and adolescents tend to react faster to medication than adult patients. The study aims to present the main prescriptions of drugs for treatment and their indications. The text is a clipping of an integrative review of the literature on depression in children and adolescents. The authors researched state that medications are capable of combating depression, but the use of antidepressants in children and adolescents has grown in recent years, factors that can be pointed out by external pressures, contributing to the physiological anxiety progressing increasingly to pathological. However, the indiscriminate use of medications is able to compromise the emotional and physical health of the patient and his/her well-being in general, especially of the infant patient, who has immunological resistance still under construction. The prescription of antidepressants should be cautious and punctual, as it requires the professional who prescribes it knowledge about the appropriate protocols for drug administration, with regard to the correct dosage of the drug, the chemical composition and the adverse reactions of the drug; in addition to the need to know details about the medical history of infant and/or adolescent patients. Thus, it is considered that the prescription of medications need to happen in a controlled manner.